Answer:
x = -251/12
Step-by-step explanation:
[tex]x+1=\frac{1}{6}+2-x--------43\\\\\mathrm{Subtract\:}1\mathrm{\:from\:both\:sides}\\\\x=\frac{1}{6}+2-x--------43-1\\\\\mathrm{Add\:}x\mathrm{\:to\:both\:sides}\\\\x+x=\frac{1}{6}+2-x--------43-1+x\\\\2x=\frac{1}{6}+2--------43-1\\\\\mathrm{Divide\:both\:sides\:by\:}2\\\\\frac{2x}{2}=\frac{\frac{1}{6}}{2}+\frac{2}{2}-\frac{ }{2}-\frac{ }{2}-\frac{ }{2}-\frac{ }{2}-\frac{ }{2}-\frac{ }{2}-\frac{ }{2}-\frac{43}{2}-\frac{1}{2}\\\\x=-\frac{251}{12}[/tex]